Conceptualizing 'Country of Ingredient Authenticity' of Luxury Brands - Zainol, Zahirah; Phau, Ian; Cheah, Isaac (Australian and New Zealand Marketing Academy, 2012)
PRADA goes local: the ‘Made In’ Campaign features its products being made in countries such as Peru, Scotland, India and Japan has proven to be something out of the ordinary and a bold move taken by the prominent luxury brand. The paper proposes a research framework to study the influence of “country of ingredient authenticity” towards product and brand evaluations of the luxury brands and the willingness to buy. Categorization theory and confirmation bias form the theoretical underpinning of the model and is structured around the research. Consumer needs for ingredient authenticity is proposed to have a direct relationship between the country cues and willingness to buy, willingness to recommend and actual purchase of luxury brand. A scale for consumer needs for ingredient authenticity will be developed alongside this research to fill the gap in the industry and research sector pertaining to consumers’ motivation to seek authentic products.